Design of the Al-Amin Living Lab and Industrial Park Mixed-Use Building in Sampe Cita Village, Kutalimbaru District - Dara Wisdianti; Peranita Sagala; Ramayana; Ivan Noor Akbar (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
. A Mixed-Use Building combines structures with different functions, such as residential, commercial, and cultural buildings, planned within a city. This research focuses on the design of a Mixed-Use Building, referring to the process of planning, illustrating, and developing a concept or idea for a building or physical structure. The study aims to understand the design of the Al-Amin Living Lab and Industrial Park Mixed-Use Building in Sampe Cita Village, Kutalimbaru District. The research material includes the site location in Sampe Cita Village, Kutalimbaru District, Deli Serdang Regency, the needs of the academic community of Panca Budi Development University for research land, and the potential for area development as a tourism facility, such as a mall and other buildings that will support the activities of the area and the surrounding community. The results of this study indicate that the facilities and infrastructure of the Al-Amin Living Lab and Industrial Park Mixed-Use Building consist of a cafe, coffee shop, meeting room, viewing area, and toilets and that the design guidelines for the Al-Amin Living Lab and Industrial Park Mixed-Use Building meet the criteria.